PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN VOUCHER INTERNET XL PADA “KONTER KUSUMA” - Beti Mei Setiyaningrum; Supriyono Supriyono (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Internet is an important requirement for the community to be able to access information easily, besides that it is also a means of communication between humans. The rapid demand for internet services, especially for internet vouchers in Indonesia, is due to the increasing number of internet users in Indonesia. The use of the internet is not only for finding information but also for communicating. This study aims to determine and analyze the effect of price perceptions and promotions on purchasing decisions for XL internet vouchers (study at "Kusuma counter" Kauman District, Ponorogo Regency). This research is included in the type of quantitative research with the method of collecting data in the form of a questionnaire. The analysis technique in this research uses the SEM method on a component basis using PLS as an analytical tool. The results of the research conducted by questionnaires were given to the respondents, totaling 66 people. The results show that price responses can contribute to purchasing decisions with the highest factor loading value on the indicator of price conformity with product quality. As for the promotion can contribute to purchasing decisions along with the highest factor loading value is the advertising indicator